2023
DOI: 10.3390/ijms241512475
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Power of Enteric Glial Cells’ Plasticity and Multipotency for Advancing Regenerative Medicine

Marie A. Lefèvre,
Rodolphe Soret,
Nicolas Pilon

Abstract: The enteric nervous system (ENS), known as the intrinsic nervous system of the gastrointestinal tract, is composed of a diverse array of neuronal and glial cell subtypes. Fascinating questions surrounding the generation of cellular diversity in the ENS have captivated ENS biologists for a considerable time, particularly with recent advancements in cell type-specific transcriptomics at both population and single-cell levels. However, the current focus of research in this field is predominantly restricted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 151 publications
0
2
0
Order By: Relevance
“…13 This study found that the levels of GFAP and GDNF were lower in UC mice compared to the normal group, indicating impaired status and function of EGCs in UC, which is consistent with previous studies. 29,30 So, in the future, whether it is possible to use levels of EGCs and other related signals, such as GDNF or p-RET, as markers of intestinal health is a question worth exploring in depth. Additionally, we validated the role of GDNF in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 This study found that the levels of GFAP and GDNF were lower in UC mice compared to the normal group, indicating impaired status and function of EGCs in UC, which is consistent with previous studies. 29,30 So, in the future, whether it is possible to use levels of EGCs and other related signals, such as GDNF or p-RET, as markers of intestinal health is a question worth exploring in depth. Additionally, we validated the role of GDNF in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Once NCCs enter the gut mesenchyme, at which point they are referred to as enteric neural-crest-derived cells (ENCDCs), they migrate along the length of the entire GI tract, to form the enteric nervous system (ENS) [2,3,5,7]. After gut colonization by vagal and sacral ENCDCs, Schwann cell precursors enter the gut alongside the extrinsic nerves [9][10][11][12][13][14][15]. Abnormal ENS formation Int.…”
Section: Introductionmentioning
confidence: 99%